Decentralized IoT Network for Sustainable Water Desalination ‎Using Bio-Membrane Nanotech - Biswas, Debarghya; Kirit , Dhablia Dharmesh; Aggarwal , Rashi (International Journal of Basic and Applied Sciences, 2025)
An innovative decentralized IoT-based desalination system based on bio-membrane nanotechnology addressing the problem of the global ‎water crisis is conceived in this research. Most conventional desalination techniques are based on centralized, energy-intensive systems, ‎which impede scalability and sustainability. By using biomembranes composed of protein-polymer hybrids designed to mimic aquaporins ‎for increased permeability and improved salt rejection, the proposed system is expected to operate effectively. The eco-friendly bio ‎membranes reduce the environmental impact. Therefore, these IoT-enabled sensors facilitate real-time monitoring of key parameters, such as ‎salinity, pressure, and membrane performance, enabling data-driven optimization of the membrane through machine learning algorithms. The ‎control system utilizes blockchain technology, which facilitates the management of multiple nodes and enables secure, self-directed decision-making. The system also uses renewable energy sources, some of which are integrated into the system, while others form self-healing ‎biopolymer coatings to minimize maintenance costs. Architecture is built on a three-layer model, composed of the perceptual, network, and ‎application layers, to ensure continuous data acquisition and processing, enabling data to inform the decision-making process. The results of ‎the experiments show a tenfold increase in desalination efficiency, accompanied by a reduction in energy consumption of up to 40% and an ‎extension of the membrane’s lifetime. In this way, the proposed solution represents a novel, scalable, cheap, and sustainable method of ‎desalination in remote or off-grid regions‎.